Total hypopharyngeal reconstruction - Sittitrai P. (2014)
In advanced hypopharyngeal carcinoma, the tumor may involve the entire hypopharyngeal mucosa and the larynx. After total laryngohypopharyngectomy is done, reconstruction of the circumferential defect of the hypopharynx is a challenge. We described our results of using a myomucosal tongue flap with dermal or skin graft (MTF) in 8 patients and using a tubed pectoralis major myocutaneous flap (TPMF) in 10 patients to reconstruct the total hypopharynx. There was no operative mortality. Fistula formation occurred in 3 patients of the MTF group and 4 in the TPMF group but all had spontaneous healing after conservative treatment. One in the MTF group and 4 in the TPMF group had stenosis of the anastomotic sites. Almost all responded well with periodic dilatation. Only one patient in the TPMF group who had been previously irradiated required gastrostomy for feeding. The 5-year actuarial survival rate of our patients was 32 per cent. These results show that total hypopharynx can be reconstructed with the above noted procedures. The survival rate is good, the morbidity rate is acceptable, and the perioperative mortality rate is zero.